Factor independent initiation of protein synthesis by IRES RNAs - Kieft, Jeffrey (Henry Stewart Talks, 2008)
Translation initiation in eukaryotes: two pathways, IRES-driven translation, Types of IRESes, IRES manipulation of ribosomes, Folding and structure of the IGR IRESes, IRES interactions with the ribosome and molecular mimicry, New IRES mechanistic models, Towards an understanding of more complex IRESes, Update interview: Relationship of IRESs to other initiation mechanisms, Update interview: Impact of diverse new techniques, Update interview: Mechanistic insights from new structures, Update interview: Future research directions and challenges
Updated at 2020/11/30